The Efficacy of Propranolol in Retinopathy of Prematurity and its Correlation with the Platelet Mass Index - Korkmaz, Levent; Bastug, Osman; Ozdemir, Ahmet; Korkut, Sabriye; KARACA, Çağatay; Akin, Mustafa Ali; GÜNEŞ, Tamer; Kurtoglu, Selim; ÖZTÜRK, Mehmet Adnan (My University, 2017)
Purpose: Retinopathy of Prematurity (ROP) is a proliferative vitreoretinopathy which is one of the most frequent causes of blindness in children. In an attempt to find a solution to this important problem in preterm children, the search for new, effective treatment modalities with fewer side effects is underway. In our study, which was planned for this reason, we aimed to investigate the effects of propranolol treatment applied to cases of ROP in various stages during the second phase (known as the neovascularization-hypoxia phase) and to determine the correlation of these effects with the platelet mass index (PMI).Method: A total of 171 preterm infants at risk of ROP were selected randomly for inclusion in the study. All of the patients were classified according to their stage of ROP and were divided into control and treatment groups. While the cases in the control group were administered physiological saline solution, those in the treatment group were administered propranolol in the period that corresponded to the second stage of the disease. The thrombocyte and PMI values in the first and second stages of each study group were recorded.Results: A significant difference was found between the control and treatment groups of the stage 2 ROP study subjects. In the stage 2 ROP study group, no significant difference was detected between the control and treatment cases in terms of platelet counts in phase 1 or in the PMI values and the thrombolytic counts in phase 2. On the other hand, in phase 2 of the stage 2 ROP study subjects significant differences were detected between the control and treatment group in terms of PMI values.Conclusion: In the study, it was found in the stage 2 ROP study group that propranolol reduced the need for laser photocoagulation significantly. Also, in parallel to the efficacy of propranolol in this study group, a decrease was observed in PMI values.